2017
DOI: 10.1002/mc.22607
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor‐β/δ inhibits human neuroblastoma cell tumorigenesis by inducing p53‐ and SOX2‐mediated cell differentiation

Abstract: Neuroblastoma is a common childhood cancer typically treated by inducing differentiation with retinoic acid (RA). Peroxisome proliferator-activated receptor-β/δ, (PPARβ/δ) is known to promote terminal differentiation of many cell types. In the present study, PPARβ/δ was over-expressed in three human neuroblastoma cell lines, NGP, SK-N-BE(2), and IMR-32, that exhibit high, medium, and low sensitivity, respectively, to retinoic acid-induced differentiation to determine if PPARβ/δ and retinoic acid receptors (RAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
0
21
1
1
Order By: Relevance
“…antagonizing PPARd inhibits tumorigenesis in lung, liver, breast, or prostate cell lines (29)(30)(31). Conversely, various studies have demonstrated that the activation of PPARd by agonists reverts or inhibits tumorigenesis in colorectal, liver, skin, breast, testicular, pancreatic cancer, or neuroblastoma cells (32)(33)(34)(35)(36)(37)(38)(39), in line with the notion that the deregulation of this nuclear receptor promotes oncogenesis in Ppard-deficient mice and colorectal cancer cells (40,41). The expression status of PPARd in cancer has been evaluated by different groups with contrasting results, which may be related to the tissue of origin and the method for quantification of PPARD levels (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…antagonizing PPARd inhibits tumorigenesis in lung, liver, breast, or prostate cell lines (29)(30)(31). Conversely, various studies have demonstrated that the activation of PPARd by agonists reverts or inhibits tumorigenesis in colorectal, liver, skin, breast, testicular, pancreatic cancer, or neuroblastoma cells (32)(33)(34)(35)(36)(37)(38)(39), in line with the notion that the deregulation of this nuclear receptor promotes oncogenesis in Ppard-deficient mice and colorectal cancer cells (40,41). The expression status of PPARd in cancer has been evaluated by different groups with contrasting results, which may be related to the tissue of origin and the method for quantification of PPARD levels (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to these reported PPAR-delta oncogenic effects, studies have also shown possible tumor suppression actions by PPAR-delta. Inhibition of cell proliferation by PPAR-delta ligands were demonstrated in a number of tumors including lung cancer, colon cancer and neuroblastoma [ 27 29 ]. Therefore the role of PPAR-delta in cancer treatment is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…79 PPARD' nin, hücre farklılaşmasını düzenleyen ve kullanılmakta olan terapide rol alan RARA ile koaktivasyonu, nö-roblastların normal diferansiyasyonunu sağlayarak nöroblastom tedavisinde yeni bir kombinasyonel yaklaşım oluşturmaktadır. 80 ALK ve CDK4/6; AURKA ve BCL2' nin dual inhibisyonları da nö-roblastom tedavisinde sinerjistik yaklaşımlar oluş-turmaktadır. [81][82][83] Epigenetik regülasyon, nöroblastomun patogenezinde olduğu kadar tedavide de büyük önem taşımaktadır.…”
Section: Hedefe Yöneli̇k Tedavi̇ Yaklaşimi Ve Gelecek Perspekti̇flerunclassified